Impact of maternal adverse childhood experiences on child socioemotional function in rural Kenya: Mediating role of maternal mental health. Issue 5 (24th April 2019) - Rieder, Amber D.; Roth, Sophia L.; Musyimi, Christine; Ndetei, David; Sassi, Roberto B.; Mutiso, Victoria; Hall, Geoffrey B.; Gonzalez, Andrea
Abstract: Mothers in low‐ and middle‐income countries (LMIC) suffer heightened vulnerability for adverse childhood experiences (ACEs), which is exacerbated by the multitude of risk factors associated with poverty and may lead to increased risk of psychiatric disorder. The constellation of complex, co‐occurring biological, environmental, social, economic and psychological risk factors are in turn transmitted to her child, conferring vulnerability for adverse development. This study examines the association between maternal intra‐ and extra‐familial ACEs, maternal education and the mental health of her child, mediated by maternal mental health. Mother‐child dyads ( n = 121) in Machakos, Kenya were examined cross‐sectionally using self‐report measures of ACEs, maternal mental health and child internalizing and externalizing mental health problems. The four models proposed to examine the relationship between intra‐ and extra‐familial maternal ACEs and child internalizing and externalizing problems demonstrated indirect pathways through maternal mental health. These effects were found to be conditional on levels of maternal education, which served as a protective factor at lower levels of maternal ACEs. These models demonstrate how the impact of ACEs persists across the lifespan resulting in a negative impact on maternal mental health and conferring further risk to subsequent generations. Elucidating the association between ACEs and subsequent intergenerational sequelae, especially in LMIC where risk is heightened, may improve targeted caregiver mental health programs for prevention and intervention. Abstract : In rural Kenya, maternal mental health is shown to mediate the relationship between maternal adverse childhood experiences (ACES) and the mental health of her children in the subsequent generation. Additionally, maternal education serves as a moderator between ACEs and mental health, where higher levels of education provide a protective buffer against mental health problems.